Inelastic electron tunneling across magnetically active interfaces in cuprate and manganite heterostructures modified by electromigration processes - Belogolovskii, M.A.; Revenko, Yu.F.; Gerasimenko, A.Yu.; Svistunov, V.M.; Hatta, E.; Plitnik, G.; Shaternik, V.E.; Rudenko, E.M. (Физика низких температур, 2002)
We report a study of the electron tunneling transport in point-contact junctions formed by a sharp Ag tip and two different highly correlated oxides, namely, a magnetoresistive manganite La₀.₆₆Ca₀.₃₄MnO₃ and a superconducting cuprate LaBa₂Cu₃O₇₋x. Strong chemical modifications of the oxide surface (supposedly, oxygen ion displacements) caused by applying high voltages to the junctions have been observed. This effect is believed to be responsible for an enormous growth of inelastic tunneling processes across a transition region that reveals itself in an overall "V"-shaped conductance background, with a strong temperature impact. The mechanism of the inelastic scattering is ascribed to charge transmission across magnetically active interfaces between two electrodes forming the junction. To support the latter statement, we have fabricated planar junctions between Cr and Ag films with an antiferromagnetic chromium oxide Cr₂O₃ as a potential barrier and at high-bias voltages have found an identical conductance trend with a similar temperature effect.